Caffeine for preterm infants: current indications and uncertainties - Nobile, S.; Carnielli, V. P. (Acta Biomedica Atenei Parmensis, 2015)
Caffeine is one of the most commonly used therapies in Neonatology, with different indications such as the treatment of apnea and the prevention of extubation failure and bronchopulmonary dysplasia. However, there are still uncertainties regarding effects on central nervous system development, time of discontinuation and dosing of the drug.